Modifying electronic and solid-state properties of fullerenes, polycyclic aromatic hydrocarbons, and perylene diimides - Clikeman, Tyler T., author; Strauss, Steven H., advisor; Rumbles, Garry, advisor; Shores, Matt P., committee member; Chen, Eugene Y.-X., committee member; Bailey, Travis, committee member; Sites, Jim, committee member (Colorado State University. Libraries, 2015)
The growing world energy demand necessitates the development of novel, cheap, and efficient energy sources and low energy consumption electronics devices. Organic photovoltaics, transistors, and light-emitting diodes are actively being developed as replacements for traditional energy sources and electronic devices. Strong electron acceptors are required to increase the efficiency and air stability for many of these applications. Studying how the incremental introduction of strong electron-accepting moieties onto electron-accepting substrates can affect performance is essential for systematically developing new devices. Furthermore, synthetic methodologies and characterization of these molecules are essential before incorporation into real world applications. This dissertation focuses on synthesizing families of strong electron acceptors via modification with strong perfluoroalkyl or cyano electron-withdrawing groups for fundamental studies in the development of advanced electronics. The first chapter focuses on the synthesis and characterization of new trifluoromethylfullerene derivatives. Synthetic methods for adding CF3 groups to C60, C70, and M3N@C80 are discussed and new CF3 addition patterns are revealed by single crystal XRD. Then the addition of electrophiles, nucleophiles, and cycloadducts to these trifluoromethylfullerene derivatives are discussed. Adding single nucleophiles and electrophiles to the cages along with collaborative DFT studies show which cage carbon atoms are most susceptible towards additional attack. The variations in electron accepting behavior were studied by adding a combination of electron-withdrawing and electron-donating groups at these specific locations on the fullerene cage. The studies revealed that these groups can modify electronic behaviors incrementally and somewhat unexpectedly by disrupting the fullerene π system. Understanding where and why new groups add to the fullerene cages and how they affect electronic behaviors could be used as the foundation for synthesizing new fullerene molecules to be used in advanced electronic devices. The second chapter concentrates on substituting electron-withdrawing fluorinated groups onto polycyclic aromatic hydrocarbon substrates. A family of poly(trifluoromethyl)azulene derivatives was synthesized and characterized for the first time. Trifluoromethylation of azulene systematically increases the electron-withdrawing strength and affects solid-state packing motifs. The molecular structures and solid-state packing of four other families of fluorine-modified polycyclic aromatic hydrocarbon substrates, corannulene, phenazine, triphenylene, and anthracene, were studied using single crystal XRD. Not only did XRD reveal previously unknown substitution patterns, but it was able to show where close π- π interactions existed within the packing structure, which could be extrapolated to solid-state charge transport in future applications. The third chapter focuses on developing a new series of perylene diimide acceptors and their use in organic photovoltaic active layers. Perylene diimides with previously unknown substitution patterns were synthesized with CF3 and CN groups and then isolated to isomeric purity using HPLC. Substituting with these strong electron-withdrawing groups at specific positions modified absorption, emission, solid-state packing, and solution- and gas-phase electron-accepting strength. These properties were compared within the entire series and solution reduction potentials were compared with a comprehensive list of literature reported perylene diimide acceptors. It was found that these properties were dependent on position and were not constant for each substituent. The series of poly(trifluoromethyl)perylene diimides were then blended with polymer donors and tested in photovoltaic active layer films. The systematic tuning of electron-withdrawing strength was used as a handle for fundamental studies on how increased electron affinity and fluorination affect charge transfer in the solid-state. All of the perylene diimides were able to accept charge from the polymer donors, but increasing the electron- withdrawing strength by introducing more fluorine atoms did not improve the charge separation yield.
Keywords: electrochemistry; fluorine; fullerene; HPLC; photovoltaics; XRD